Construction and Application of a Coupled Temperature and Pressure Model for CO2 Injection Wells Considering Gas Composition - Hang Lai; Peng Chen; Lingang Lv; Song Lu (Energies)
Accurate prediction of the temperature and pressure fields in carbon dioxide (CO2) injection wells is critical for enhancing oil recovery efficiency and ensuring safe carbon sequestration. At present, the prediction model generally assumes that CO2 is pure and does not consider the influence of impurities in CO2 components. This study takes into account the common impurities, such as air and various alkanes in CO2, and uses Refprop 9.0 software to calculate the physical parameters of the mixture. A comprehensive coupling model was developed to account for axial heat conduction, convective heat transfer, frictional heat generation, the soup coke effect, pressure work, and gas composition. The model was solved iteratively using numerical methods. We validated the accuracy of the calculated results by comparing our model with the Ramey model using measured injection well data. Compared with the measured bottom hole temperature and pressure data, the error percentage of our model to predict the bottom hole temperature and pressure is less than 1%, while the error percentage of Ramey model to predict the bottom hole temperature and pressure is 5.15% and 1.33%, respectively. Our model has higher bottom hole temperature and pressure prediction accuracy than the Ramey model. In addition, we use the model to simulate the influence of different injection parameters on wellbore temperature and pressure and consider the influence of different gas components. Each injection parameter uses three components. Based on the temperature and pressure data calculated by the model simulation, the phase state of CO2 was analyzed. The results show that the impurities in CO2 have a great influence on the predicted wellbore pressure, critical temperature, and critical pressure. In the process of CO2 injection, increasing the injection pressure can significantly increase the bottom hole pressure, and changing the injection rate can adjust the bottom hole temperature. The research provides valuable insights for CO2 sequestration and enhanced oil recovery (EOR).